Strengthening activeness and learning interest in mathematics through problem-based learning among Grade XI Students - Fitri Andriani; Z. Zukhrufurrohmah; Alfi Nelli (Jurnal Pendidikan Profesi Guru, 2024)
Based on the initial classroom observation in class XI-I, it was found that several students were passive and lacked enthusiasm during mathematics lessons. This was attributed to low curiosity about the subject matter and the use of monotonous teaching models. This study is a Classroom Action Research (CAR) aimed at increasing student activeness and learning interest in mathematics through the implementation of the Problem-Based Learning (PBL) model. The research subjects were 36 students of class XI-I in the 2023/2024 academic year. Data collection techniques included observation of student activeness, learning interest, implementation of learning, and learning interest questionnaires. The results indicated a positive impact of PBL on the learning process, with student activeness increasing by 9.44%, learning interest by 9.03%, questionnaire scores by 6.94%, and the implementation of the learning model by 5.95%. These findings suggest that Problem Based Learning is effective in improving students' activeness and interest in learning mathematics.